Gender interventions in pig-related businesses in Masaka and Mukono districts, Uganda: Pig value chain - Achandi, Esther; Namatovu, Jane; Ebanyat, Pamela; Lambuli, Joyce; Malali, Gudoi Noah; Nahwaya, Agnes; Immaculate, Omondi; Ouma, Emily A.; Galie, Alessandra (International Livestock Research Institute, 2024)
Pig farming is widely practised in all regions of Uganda, with high concentrations around Central Region (Mulindwa 2016). Engagement in piggery offers a means to empower women. However, women are mostly involved in the production node of the pig value chain and are largely absent from the higher value nodes, mainly due to gender norms that inhibit them from specific and often more lucrative activities in pig-related businesses. Gender norms define acceptable and appropriate actions for women and men (across other characteristics such as age, ethnicity and religion) in a given group or society at a given time (Cislaghi and Heise 2020). To sustainably progress towards gender equity, restrictive gender norms (such as those that limit women’s mobility, decision-making and resource ownership) and gaps in empowerment need to be addressed.